Changes in heart rate and blood lactate concentration as intensity parameters during simulated Taekwondo competition - Butios, S.; Tasika, N. (The Journal of Sports Medicine and Physical Fitness, 2007)
Aim: The absence of studies related to physiological responses in athletes during Taekwondo competition makes this the first attempt to investigate the physical aspects of this relative new Olympic sport event. Therefore, the aim of this study was to record and analyze heart rate (HR) and blood lactate (BL) levels of elite male Taekwondo athletes during multiple competition bouts in a single day. Methods: Experimental design: prospective. Setting: competition simulation. Participants: 24 elite male athletes, aged 20 to 24 years. Measures: HR and BL responses were studied on 24 national level Taekwondo players in multiple competition bouts to explore the aerobic-anaerobic metabolism, as well as the physical demands of the players. The aerobic capacity (V.O2max) of the players were determined using a 20 m shuttle run test. HR and BL concentration levels were measured during warm up and fighting rounds in every competition bout. Results: The mean V.O2max ability for all subjects was 53.92 mL/kg/min and there was no significant difference between groups. Only the heavy weight division (+80 kg) players demonstrated a significant higher HRmax (P<0.05) than the other two divisions. No inter-weight division, as well as inter-round differences, were observed in the HR and BL concentration levels of the players. After all divisions were recorded and analyzed the mean HR and BL levels during competition were 158 beats/min and 3.35 mmol/L, respectively. Conclusion: The study highlights that in competitive Taekwondo, irrespective of the weight division or aerobic capacity, the anaerobic adaptability of the subjects is the same.